1979
DOI: 10.1210/jcem-49-5-687
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Progesterone, Androgens, and Estrogens by Granulosa Cells, Thecal Tissue, and Stromal Tissue from Human Ovaries in Vitro *

Abstract: The concentrations of steroids in antral fluid, the number of granulosa cells, the status of the oocyte, and the diameter of each follicle were determined in human ovaries so that follicles at each stage of the menstrual cycle could be classified as large (greater than or equal to 8 mm diameter) or small (less than 8 mm diameter) and healthy or atretic. The granulosa cells and thecal-enriched tissue from each follicle and the stromal tissue from each ovary were cultured for 6 days in vitro. The amounts of prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0
4

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(125 citation statements)
references
References 25 publications
3
116
0
4
Order By: Relevance
“…Tsang et al found that the granulosa cells produced little or no androgen, even with FSH added to the culture medium (23). However, McNatty et al found that P, E2,'T, and androstenedione did accumulate in the medium of granulosa cells cultured in vitro and proposed that the granulosa cells of most follicles were capable of de novo synthesis of all of these steroids (24).…”
Section: Discussionmentioning
confidence: 99%
“…Tsang et al found that the granulosa cells produced little or no androgen, even with FSH added to the culture medium (23). However, McNatty et al found that P, E2,'T, and androstenedione did accumulate in the medium of granulosa cells cultured in vitro and proposed that the granulosa cells of most follicles were capable of de novo synthesis of all of these steroids (24).…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies of follicular epithelium in vitro have generally shown that these cells possess an aromatase system capable of converting androgen to oestrogen, but, with the exception of human follicles (McNatty et al 1979), little or no ability to synthesize androgens. However, they are capable of synthesizing progesterone in vitro, a capacity which is greater in preovulatory follicles, particularly after the stimulus of an LH surge or in response to LH added to the medium (see Richards 1980).…”
Section: Follicular Epitheliummentioning
confidence: 99%
“…Whether any significant oestrogen production occurs in the theca is less certain, although there are data in the pig (Rodway et al 1975;Stoklosowa et al 1978), Rhesus monkey (Channing and Coudert 1976) and man (McNatty et al 1979) to suggest that this may be so in some species.…”
Section: Theca Internamentioning
confidence: 99%
See 1 more Smart Citation
“…These androgens are transferred to the preovulatory granulosa cells, where the androstenedione and testosterone are aromatized to estrone and estradiol by 17-b-hydroxysteroid dehydrogenase type I, stimulated by FSH (9). The ovarian androgen production and its conversion to estradiol are essential to the physiologic ovulatory process, and an insufficient androgen production at the follicular phase can lead to anovulation (10).…”
mentioning
confidence: 99%